2017
DOI: 10.3892/mmr.2017.7555
|View full text |Cite
|
Sign up to set email alerts
|

High expression of endoglin in primary breast cancer may predict response to neoadjuvant chemotherapy

Abstract: Neoadjuvant chemotherapy (NAC) is a widely-used treatment for breast cancer, as it may render unresectable breast tumors to become resectable. In addition, NAC provides the unique opportunity to assess response to treatments within months rather than years of follow-up. However, predictive markers of tumor response to NAC are lacking. Therefore, the present study aimed to investigate the expression of endoglin, a marker of angiogenesis, and its association with pathologic responses to NAC. Samples from 34 brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…ENG is a protein primarily upregulated during angiogenesis, and can inhibit cell migration, invasion, and metastatic colonization in vitro and in vivo by mitigating the effects of transforming growth factor beta protein (TGF-β), which is activated during the invasion and migration oncogenic stages [ 60 ]. Thus, elevated ENG expression is associated with an improved primary tumor response rate for neoadjuvant therapy, which is correlated with improved clinical outcomes in several studies [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…ENG is a protein primarily upregulated during angiogenesis, and can inhibit cell migration, invasion, and metastatic colonization in vitro and in vivo by mitigating the effects of transforming growth factor beta protein (TGF-β), which is activated during the invasion and migration oncogenic stages [ 60 ]. Thus, elevated ENG expression is associated with an improved primary tumor response rate for neoadjuvant therapy, which is correlated with improved clinical outcomes in several studies [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-CD105 antibodies have shown a high affinity for activated endothelial cells in tissues associating angiogenesis and are considered as a therapeutic option for patients with breast cancer, especially of triple-negative type. 114,115 The preliminary study of CD105 staining revealed that microvascular density has a positive and negative relationship, respectively, with HER2 and hormone receptor expression. Consequently, targeting CD105 was suggested as a potential strategy in the anticancer treatment approach.…”
Section: Syndecanmentioning
confidence: 99%
“…Endoglin, also named CD105, is expressed on the endothelial cells of around- and within-tumor blood vessels as well as overexpressed in tumor stromal components. The anti-CD105 antibodies have shown a high affinity for activated endothelial cells in tissues associating angiogenesis and are considered as a therapeutic option for patients with breast cancer, especially of triple-negative type 114,115 . The preliminary study of CD105 staining revealed that microvascular density has a positive and negative relationship, respectively, with HER2 and hormone receptor expression.…”
Section: Endoglinmentioning
confidence: 99%